Assessment of Thermal Comfort at Classroom Environment: Subjective Measurement vs. Direct Technical Measurement - Isa, Halim; Rohana, Abdullah (2008)
Thermal comfort is a condition of mind which expresses satisfaction with the surrounding thermal environment. In classroom, thermal comfort must be managed efficiently since poor condition of thermal comfort has negatively influencing students’ concentration and lecturer’s performance. In recognition the importance of thermal comfort in the classroom, the objective of the study is to assess thermal comfort at classroom environment in a Malaysian public university. Subjective measurement associated with questionnaires was applied to identify occupants perceptions regarding to thermal environment in their classrooms, and at the same time, direct measurement of thermal comfort was carried-out using a thermal comfort monitor. Six classrooms were measured i.e. BK 1, BK 5, BK 10, BK 12, BK 13, and BK 17. Based on both measurement techniques, BK 13 was identified as the most satisfied thermal environment among others during morning session and afternoon session, and BK 12 was found to be most satisfied thermal environment at evening session. Statistical analysis concluded that there is a good agreement between subjective measurement and direct technical measurement for those classrooms as both methods show a positive correlation. In the other word, the direct technical measurement technique has confirmed the occupants’ perceptions.